Atrial Substrate and Triggers of Paroxysmal Atrial Fibrillation in Patients With Obstructive Sleep Apnea. (November 2017) - Anter, Elad; Di Biase, Luigi; Contreras-Valdes, Fernando M.; Gianni, Carola; Mohanty, Sanghamitra; Tschabrunn, Cory M.; Viles-Gonzalez, Juan F.; Leshem, Eran; Buxton, Alfred E.; Kulbak, Guy; Halaby, Rim N.; Zimetbaum, Peter J.; et al.
Abstract : Background: Obstructive sleep apnea (OSA) is associated with atrial remodeling, atrial fibrillation (AF), and increased incidence of arrhythmia recurrence after pulmonary vein (PV) isolation. We aimed to characterize the atrial substrate, including AF triggers in patients with paroxysmal AF and OSA. Methods and Results: In 86 patients with paroxysmal AF (43 with ≥moderate OSA [apnea–hypopnea index ≥15] and 43 without OSA [apnea–hypopnea index <5]), right atrial and left atrial voltage distribution, conduction velocities, and electrogram characteristics were analyzed during atrial pacing. AF triggers were examined before and after PV isolation and targeted for ablation. Patients with OSA had lower atrial voltage amplitude (right atrial, P =0.0005; left atrial, P =0.0001), slower conduction velocities (right atrial, P =0.02; left atrial, P =0.0002), and higher prevalence of electrogram fractionation ( P =0.0001). The areas of atrial abnormality were consistent among patients, most commonly involving the left atrial septum (32/43; 74.4%). At baseline, the PVs were the most frequent triggers for AF in both groups; however, after PV isolation patients with OSA had increased incidence of additional extra-PV triggers (41.8% versus 11.6%; P =0.003). The 1-year arrhythmia-free survival was similar between patients with and without OSA (83.7% and 81.4%, respectively; P =0.59). In comparison, control patients with paroxysmal AF and OSA who underwent PV isolation alone without ablation on extra-PV triggers had increased risk of arrhythmia recurrence (83.7% versus 64.0%; P =0.003). Conclusions: OSA is associated with structural and functional atrial remodeling and increased incidence of extra-PV triggers. Elimination of these triggers resulted in improved arrhythmia-free survival.